1965
DOI: 10.1021/ja00949a033
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Electron-Transfer Oxidation of Alkyl Radicals by Copper(II) Complexes

Abstract: That the decrease in R, on monosubstitution in the 3position, is not reflected in a change of may be attributed to the only other variable in eq. 5, i.e., DE. The term DE is a dielectric constant in name only, being a function of the shape of the molecule (for a spherical model the square of the ratio of the distance of the protons from the center of the sphere and the radius of the sphere), the dielectric constant of the molecule, and the dielectric constant of the solvent.The lack of sensitivity of ^ to chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(35 citation statements)
references
References 5 publications
5
30
0
Order By: Relevance
“… 31 Consistent with this observation, Kochi reported that nitrogen-ligated Cu(II) complexes oxidize alkyl radicals to alkenes more slowly than do simple Cu(II) salts. 32 , 33 Although these reactions with ligated copper occurred in lower yield than those with simple copper halides, they did give substantial amounts of product and were valuable for studying the mechanism of this reaction ( vide infra ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 31 Consistent with this observation, Kochi reported that nitrogen-ligated Cu(II) complexes oxidize alkyl radicals to alkenes more slowly than do simple Cu(II) salts. 32 , 33 Although these reactions with ligated copper occurred in lower yield than those with simple copper halides, they did give substantial amounts of product and were valuable for studying the mechanism of this reaction ( vide infra ).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism for the initial conversion of cyclohexane to cyclohexene likely proceeds by abstraction of a hydrogen atom from cyclohexane by a tert -butoxy radical to generate a cyclohexyl radical, which undergoes oxidation to the alkene. The oxidation of alkyl radicals to olefins by copper–peroxide systems has been studied by Kochi 32 , 39 and Walling. 40 Their studies imply that oxidation of the cyclohexyl radical formed in the current system likely generates cyclohexyl cation, which undergoes deprotonation to form the alkene.…”
Section: Resultsmentioning
confidence: 99%
“…Although there is little quantitative information regarding the rates of 1,4-aryl migrations, these reactions would appear to be reasonably fast when they are strongly exothermic as, for example, in the conversion of a primary alkyl radical to a tertiary (87) (compare the 1,2-aryl shifts). By utilizing data concerning the cyclization (both Ar r 5 and Ar 2 -6) of 4-phenylbutyl and its oxidation by cupric ion (93) and accepting a value of ~10 8 M" 1 sec -1 as the rate constant for the oxidation (94), the rate constant for the cyclization can be calculated to be ca. 1-5 x 10 4 sec" 1 at 150°C.…”
mentioning
confidence: 99%
“…93 94 7-Octenyl radicals undergo slow but regiospecific 1,7 ring closure [k lt7 « 7 x 10 2 sec -1 at 65°C (755)]. 93 94 7-Octenyl radicals undergo slow but regiospecific 1,7 ring closure [k lt7 « 7 x 10 2 sec -1 at 65°C (755)].…”
mentioning
confidence: 99%
“…The copper-catalyzed allylic oxidation (KharashSosnovsky reaction) of olefins with peresters has been the subject of numerous synthetic and mechanistic investigations [1][2][3][4][5][6][7][8][9][10]. The allylic ester product of the reaction can easily be converted into allylic alcohol by saponification or reduction method.…”
Section: Introductionmentioning
confidence: 99%